SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TEMPAT KULINER BERBASIS ANDROID MENGGUNAKAN MODEL FUZZY MAMDANI - Zulqifli, Sandhi; sutikno, sutikno (STKIP PGRI Tulungagung, 2017)
Culinary is a part of life that is closely related to the daily food consumption. Some people have difficulty in determining places to be visited for eating, it is affected by several considerations, such as the budget and the facilities at the eating place.The purpose of this paper is to build an application on the culinary recommendations in Semarang used Mamdani Fuzzy Model with android-based. This application had a function to give recommendation based on budget and facilities selected by the user used Mamdani Fuzzy Model. This application is Android based with Javascript programming language and Ionic framework. Applications can be used on Android smartphone connected to the Internet, then give recommendations based on budget and the facilities selected by the user.